2016
DOI: 10.1002/aic.15236
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance polymer‐supported extractants with phosphonate ligands for scandium(III) separation

Abstract: in Wiley Online Library (wileyonlinelibrary.com) As the market demand for scandium has grown, a great deal of interest has been generated in its recovery. To substantially simplify the process and provide a green alternative for scandium separation, novel polymer-supported extractants containing di(2-ethylhexyl) phosphonate and bis(2,4,4-trimethylpentyl) phosphonate, [D201][DEHP] and [D201] [C272] are proposed because they demonstrate improved adsorption capacity and selectivity toward scandium(III). Scand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Different types of sorbents have been reported for the sorption of scandium from dilute solutions, including (a) biosorbents such as yeast [17], bacteria [18] or algae [19], carbon-based materials [20], resins [21][22][23][24]; impregnated resins [25][26][27]. Recently a new generation of materials has been designed using the interactions of alginate and polyethyleneimine (PEI) for manufacturing bead sorbents [28].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of sorbents have been reported for the sorption of scandium from dilute solutions, including (a) biosorbents such as yeast [17], bacteria [18] or algae [19], carbon-based materials [20], resins [21][22][23][24]; impregnated resins [25][26][27]. Recently a new generation of materials has been designed using the interactions of alginate and polyethyleneimine (PEI) for manufacturing bead sorbents [28].…”
Section: Introductionmentioning
confidence: 99%
“…The interference of Si(IV) was not studied because it is generally not present in the sulfuric acid leachate of Sc(III). 8,16,52,53 Figure 5 shows the plots of the degree of extraction of the metal ions listed above from a 0.1 mol dm –3 H 2 SO 4 /(NH 4 ) 2 SO 4 solution with 50 mmol dm –3 D2EHAG or D2EHAF as a function of the equilibrium pH.…”
Section: Resultsmentioning
confidence: 99%
“…Solvent extraction of various metal ions [i.e., Sc­(III), Fe­(III), Ni­(II), Al­(III), Co­(II), Mn­(II), Cr­(III), Ca­(II), and Mg­(II)] was performed using D2EHAG and D2EHAF. The interference of Si­(IV) was not studied because it is generally not present in the sulfuric acid leachate of Sc­(III). ,,, Figure shows the plots of the degree of extraction of the metal ions listed above from a 0.1 mol dm –3 H 2 SO 4 /(NH 4 ) 2 SO 4 solution with 50 mmol dm –3 D2EHAG or D2EHAF as a function of the equilibrium pH.…”
Section: Resultsmentioning
confidence: 99%
“…Solid–liquid extraction (SLE) has emerged as an attractive alternative for Sc extraction due to the elimination of toxic, inflammable, and expensive organic solvents (diluent + extractant) and the facile reuse of adsorbent materials . A number of adsorbent materials have been developed for Sc recovery, including polyelectrolytes, carbon-based materials, polymer resins, and silica. These adsorbents exhibit high Sc adsorption capacity owing to their high surface area and abundant negatively charged functional groups, , but their utility to extract Sc in the presence of competing lanthanides remains largely unknown, a barrier for their application to low-grade Sc feedstocks. ,,,,, Microbe-mediated surface adsorption (biosorption) via metal complex formation with the surface functional group offers a potentially cost-effective and environmentally sustainable approach for SLE of REE from dilute feedstock sources. Previous work has shown that Sc was preferentially adsorbed to Bacillus subtilis and Escherichia coli when Sc was present at the same concentrations as the lanthanides. , Several yeast species were found to preferentially adsorb Sc over Y, Fe, and Al in both synthetic solutions and red mud leachates . While these initial studies are promising, it remains an open question, however, whether biosorption can be effectively applied for selective and scalable Sc recovery from relevant industrial feedstocks.…”
Section: Introductionmentioning
confidence: 99%
“…17−32 These adsorbents exhibit high Sc adsorption capacity owing to their high surface area and abundant negatively charged functional groups, 25,32 but their utility to extract Sc in the presence of competing lanthanides remains largely unknown, a barrier for their application to lowgrade Sc feedstocks. 18,22,23,26,27,32 Microbe-mediated surface adsorption (biosorption) via metal complex formation with the surface functional group offers a potentially cost-effective and environmentally sustainable approach for SLE of REE from dilute feedstock sources. 33−36 Previous work has shown that Sc was preferentially adsorbed to Bacillus subtilis and Escherichia coli when Sc was present at the same concentrations as the lanthanides.…”
Section: ■ Introductionmentioning
confidence: 99%